Juridical Analysis of the Judge's Consideration in Terms of Mitigating the Defendant Against Premeditated Murder According to Law Number 48 of 2009 Concerning Judicial Power - Parlindungan Siregar; Risdalina Risdalina; Indra Kumala Sari M (Journal of Social Research, 2022)
Background: The law governing the National Criminal Procedure Law must be based on the views/philosophies of national life and the basis of the state, therefore the provisions of articles or paragraphs contained in the National Criminal Procedure Law describe the protection of human rights and the obligations of citizens. Objectives: This study aims to find out and analyze things that can be considered aggravating circumstances and mitigating circumstances in criminal convictions. As well as knowing and analyzing the effect of consideration of burdensome circumstances and mitigating circumstances in criminal convictions Methods: This research belongs to the normative type of research. So that it can be known that the matters that can be considered as aggravating circumstances and mitigating circumstances in the judgment of conviction must be by the characteristics. Result: The most important consideration of aggravating and mitigating circumstances affects the proportionality of criminal convictions, both the proportionality between the criminal act imposed and the degree of guilt committed by the defendant, the proportionality related to the disparity of the verdict, and the proportionality between the conviction and the profits obtained from the criminal act. Conclusion: The form is in the form of the nature, subject, atmosphere, or situation that prevails, relating to the criminal act. The formulation is found outside of the criminal act itself outside the elements of the criminal act and describes the seriousness of the crime or the degree of danger of the perpetrator, which affects the size of the severity of the crime to be imposed.